DESIGN AND DEVELOPMENT OF AUGMENTATIVE AND ALTERNATIVE DIGITAL HOME CONTROL INTERFACE - Matteo Pastorino; Juan Bautista Montalvá Colomer; María Teresa Arredondo; Maria Fernanda Cabrera-Umpiérrez (Journal of Accessibility and Design for All, 2013)
An inquiry of the National Statistics Institute of Spain shows that 74% of the Spanish population with disabilities suffers some kind of limitation performing Daily Basic Activities, while 1.39 million cannot perform them at all without the assistance of specialized personnel. Digital Home Systems could mitigate disabled people’s difficulties to carry out those activities, giving the opportunity to manage home appliances through a single control. Digital Home Systems have to provide specific and adapted control interfaces based on Augmentative and Alternative Communication languages in order to be an efficient solution to the problem and to allow most vulnerable groups of people with disabilities to reach the highest level of autonomy.  This paper describes a Digital Home Interface capable of adapting layouts, styles and contents to device capability, user preferences and appliances’ features; designed with a combination of web technologies, standard languages for abstract interface definition and AAC systems.